THE PROFESSIONAL DEVELOPMENT OF EMPLOYEES ENGAGED IN THE ORGANIZATION OF CONSTRUCTION PRODUCTION - M. Barbarskaya (Вестник университета)
The article substantiates the need to improve the skills of workers engaged in the organization of construction production from two points of view: from the point of view of the legislation governing construction activities and from the point of view of the functioning of the market mechanism. On the example of the Samara region the estimation of labor resources engaged in construction, in particular the level of their education. The requirements for employees of construction companies necessary for entry into self-regulatory organizations, as well as the forms and directions of training of workers engaged in the organization of production in construction.